Short interest and stock price crash risk - Callen, Jeffrey L.; Fang, Xiaohua (Journal of Banking & Finance, 2015)
Using a large sample of U.S. public firms, we find robust evidence that short interest is positively related to one-year ahead stock price crash risk. The evidence is consistent with the view that short sellers are able to detect bad news hoarding by managers. Additional findings show that the positive relation between short interest and future crash risk is more salient for firms with weak governance mechanisms, excessive risk-taking behavior, and high information asymmetry between managers and shareholders. Empirical support is provided showing that the relation between short interest and crash risk is driven by bad news hoarding.